Carta de Ángela Belaval a Emilio S. Belaval y Josefina González Sicardo - Belaval, Ángela; Belaval, Emilio S.; González Sicardó, Josefina (My University, 1966)
Carta personal sobre la salud de un familiar.
Keywords: Belaval, Angela--Correspondence.; Belaval, Angela--Correspondencia.; Belaval Maldonado, Emilio S.--Correspondence.; Belaval Maldonado, Emilio S.--Correspondencia.